Hadith Interpretation from a Gender Perspective: Maqāṣid and Women’s Experience in Indonesian Fatwas - Faqiuddin Abdul Kodir; Zunly Nadia (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2026)
Despite documented health risks and persistently high prevalence rates, the Indonesian government long deferred decisive regulatory action on female circumcision. This action reflects a hesitation shaped by the Indonesian Council of Ulama (MUI)'s 2008 fatwa, which framed the practice as a legitimate Islamic observance that the state had no authority to prohibit. This regulatory impasse persisted for over a decade, during which public health objectives remained subordinated to religious normative authority. The situation shifted only after the Indonesian Women Ulama Congress (KUPI) issued its fatwa in 2022, providing the Islamic legal legitimacy that enabled the government to formally ban the practice through Government Regulation No. 28 of 2024. The debated ḥadīth corpus — the principal textual basis for legal reasoning on female circumcision, understood as a pre-Islamic cultural practice that acquired religious associations within the Islamic juristic tradition — is interpreted through divergent maqāṣid-based methodologies with profoundly different epistemological and policy consequences. Utilising qualitative textual analysis of both fatwas, this article addresses two interrelated questions: how MUI and KUPI differ in their maqāṣid frameworks mediating the relationship between ḥadīth authority and ethical evaluation, and to what extent women’s actual experiences are recognised as epistemically relevant in the assessment of contested prophetic reports. The findings reveal two contrasting orientations: MUI deploys maqāṣid primarily as regulatory constraints that preserve inherited juristic precedent, while KUPI incorporates women’s experiential knowledge as a constitutive interpretive input that reconfigures the evaluation of ḥadīth authority in light of Qur'ānic and Sunnah-based commitments to preventing harm, maintaining dignity, and providing justice. By demonstrating how gendered epistemologies reshape the interpretive function of maqāṣid in ḥadīth analysis, this article contributes to debates on Islamic legal methodology, religious authority, and policy legitimacy in Muslim-majority societies. Keywords: hadith interpretation; maqāṣid al-Sharīʿah; female circumcision; women's lived experience; gendered epistemology.